Factors Involved in Removing the Non-Structural Protein of Foot-and-Mouth Disease Virus by Chloroform and Scale-Up Production of High-Purity Vaccine Antigens - Sun Young Park; Sim-In Lee; Jong Sook Jin; Eun-Sol Kim; Jae Young Kim; Ah-Young Kim; Sang Hyun Park; Jung-Won Park; Soonyong Park; Eun Gyo Lee; Jong-Hyeon Park; Young-Joon Ko; et al. (Vaccines, 2022)
Foot-and-mouth disease (FMD) is an economically important and highly infectious viral disease, predominantly controlled by vaccination. The removal of non-structural proteins (NSPs) is very important in the process of FMD vaccine production, because vaccinated and naturally infected animals can be distinguished by the presence of NSP antibodies in the FMD serological surveillance. A previous study reported that 3AB protein, a representative of NSPs, was removed by chloroform treatment. Therefore, in this study, the causes of 3AB removal and factors affecting the effect of chloroform were investigated. As a result, the effectiveness of chloroform differed depending on the virus production medium and was eliminated by detergents. In addition, it was found that 3AB protein removal by chloroform is due to the transmembrane domain of the N-terminal region (59–76 amino acid domain). Further, industrial applicability was verified by applying the chloroform treatment process to scale-up FMD vaccine antigen production. A novel downstream process using ultrafiltration instead of polyethylene glycol precipitation for high-purity FMD vaccine antigen production was established. This result will contribute toward simplifying the conventional process of manufacturing FMD vaccine antigens and ultimately reducing the time and cost of vaccine production.